SUBSTITUSI PEMBUATAN KERUPUK IKAN LELE DENGAN PENAMBAHAN REBUNG (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2022)
Crackers is one type of dry food made from ingredients that contain high starch and is a type of snack that experienced volume development and has a low density during the frying process. The objective of the study was to determine the best composition between snakehead fish meat, tapioca with bamboo shoots in making crackers and to determine the physical and chemical content. The test conducted in this research was water content, ash content, bloom test, and organoleptic tests. In this calculation using the bait of snakehead fish, bamboo shots and tapioca flour, with 3 treatments that was A1 (snakehead fish of 500 g: taro flour of 0 g: tapioca of 500 g), A2 (snakehead fish of 250 g: bamboo shoots of 250 g: tapioca of 250 g), A3 (snakehead fish of 125 g: bamboo shoots of 500 g: tapioca of 125 g). The results showed that the most preferred treatment by panelists was treatment of A1. Treatment on snakehead fish cracker manufacturing with substitution of taro flour had the average value of water content and ash content was 3.29% and 1.72% respectively. The blooming test at treatment of A1 had the highest bloom rate (328.31) compared to A2 and A3 treatments.